Effect of Combination of Achillea millefolium, Artemisia absinthium & Juglans regia Leaves Extracts on Leishmania Major (MRHO/IR/75/ER), In vitro - N Yektaeian; M Rafeian; B Khalili-Dehkordi; SH Hejazi; L Shirani - Bidabadi; SA Hosseini (Institue of Medicinal Plants, ACECR, 2012)
Background : Due to side effects of the drug and also tendency of people in using herbal medicine, this study aimed to evaluate the sinerjhist effects of three herbs Achillea millefolium, Artemisia absinthium and Juglans regia leaf combained extract on Leishmania major, so that in case of effectiveness in further studies possible alternative drugs can be formulated.   Objective : Access to formulation drug without harmful chemical material and without side effects.   Methods : In an experimental study four tubes were selected and the mixture of three herbs leaf extracts with concentrations of 25 mg/ml were prepared. After 6, 12, 24, 48 and 72 hours sample were tested for dead or alive and also for their mobility of the parasite. Data were analyzed by ANOVA test.   Results : This study showed that combaind extracts of these three herbs caused an increase in immobility of the parasites. The rate of immobility had direct relationship with time and immobility was continuously increased after 24, 48 and 72 hours. The result were suggestive that three herbs leaf hydroalcoholic extracts were significantly more effective in reduction of parasite, in vitro (p<0.05) however, Glucantime after 24 hours and amphotericin B after 30 minute caused immobility of parasite versus 24 hour for plant extract. Conclusion : Our study showed that the extracts of three mentioned herbs had effect on growth of Leishmania major, however further studies are needed to show effects of these herbs in animal models and voluntary infected people.